Dexamethasone induced severe paralysis hypokalemia: A case report - Rizaldy Taslim Pinzon; Nathania Fadjarsugeng (Romanian Journal of Neurology, 2023)
Acute weakness related with hypokalemia periodic paralysis (HPP) is a rare clinical condition. The one common etiology of hypokalemia is the shifting of potassium into the cells. The common provoke factors are high-carbohydrate diet, heavy exercise, stress, extreme cold weather, alcohol consumption, and certain medications. We present the case of a 32‐year‐old Javanese male with an acute onset of bilateral lower and upper limb weakness with severe hypokalemia following dexamethasone injection. He was diagnosed with HPP. Our systematic review found similar cases, with possible pathophysiology explanation. Steroids should be considered as an unusual precipitating factor while managing patients with HPP.